Application of neural based fuzzy logic sliding mode control with moving sliding surface for the seismic isolation of a building with active tendon - Yakut, O.; Alli, H. (Ios Press, 2009)
In this study, neural based fuzzy sliding mode control algorithm is designed by putting advantageous specifications of sliding mode control and artificial intelligence techniques and applied to 8 storey sample building with active tendon. Performance of the designed controller is examined by applying acceleration data belonging to 6 earthquakes, each having different characteristics, as the external driving force. MATLAB software is used for numerical solutions, and the obtained results are compared in graphical form and presented in tables. Genetic algorithm is used for optimization process. Parametric uncertainities and time delay effects are considered. It is observed that performance of the controller is quite high and control force can be used practically. The obtained results also show that the controller provides quite successful control under earthquake effects having different characteristics.
Keywords: Seismic isolation; Fuzzy logic; Artificial neural networks; Moving sliding surface; Sliding-mode control; Genetic algorithm